The Role of Military Training Faculties of Higher Educational Institutions in the Preparation of the Mobilization Reserve of the Armed Forces of the Republic of Uzbekistan - Turakhanov Akrom Abdullakhakimovich; Mehmonaliev Shohmukhammad Muzaffar ugli (Zien Journals, 2022)
this article covers topics such as: preparation of the mobilization reserve of the armed forces and trends in the formation and development of the accumulative system; stages of preparation of the military-trained; reserve; indicators characterizing the training subsystem; elements of the Mobilization Conscription reserve and initial training that determine internal indicators (parameters); description of the indicators of the subsystem of accounting and accumulation of the mobilization reserve.
Keywords: mobilization; resource; reserve; accounting